2019
DOI: 10.1002/jbmr.3801
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in the Mechanical Regulation of Bone Healing Are Explained by Altered Cellular Mechanoresponse

Abstract: Increasing age is associated with a reduced bone regeneration potential and increased risk of morbidities and mortality. A reduced bone formation response to mechanical loading has been shown with aging, and it remains unknown if the interplay between aging and mechanical stimuli during regeneration is similar to adaptation. We used a combined in vivo/in silico approach to investigate age-related alterations in the mechanical regulation of bone healing and identified the relative impact of altered cellular fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 60 publications
(74 reference statements)
3
40
0
Order By: Relevance
“…Specifically, we saw that the initiation of bone formation (maximum in week 2-3), indicating the onset of the reparative phase, triggered bone resorption (maximum in week 3-4) with maximum osseous callus volumes in week 3. These observations are in line with cross-sectional histomorphometric analyses in similar defect models, where maximum callus area was seen in weeks 2 and 3 3739 . From week 4 to week 6, bone formation and resorption continuously decreased to levels (BFR ≤ 1%/day; BRR ≤ 0.8%/day) seen in normal bone remodeling of trabecular and cortical bone in mice 14,4043 , indicating proceeding towards the end of the healing process.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Specifically, we saw that the initiation of bone formation (maximum in week 2-3), indicating the onset of the reparative phase, triggered bone resorption (maximum in week 3-4) with maximum osseous callus volumes in week 3. These observations are in line with cross-sectional histomorphometric analyses in similar defect models, where maximum callus area was seen in weeks 2 and 3 3739 . From week 4 to week 6, bone formation and resorption continuously decreased to levels (BFR ≤ 1%/day; BRR ≤ 0.8%/day) seen in normal bone remodeling of trabecular and cortical bone in mice 14,4043 , indicating proceeding towards the end of the healing process.…”
Section: Discussionsupporting
confidence: 89%
“…These commercially available rigid external fixators are widely used in fracture healing studies as they also allow for the assessment of biomaterials in non-union defects (induced by increasing the defect size). Borgiani et al 37 have recently extensively characterized the healing process (week 1-3) using external fixators of similar stiffness and observed endochondral ossification processes, albeit less pronounced compared to semi-rigid fixation. When comparing the outcome of these studies using rigid fixation, it is important to consider differences in defect sizes: 0.7mm 2 , 1.19±0.25 mm 44 , 1.47±0.16mm (this study).…”
Section: Discussionmentioning
confidence: 99%
“…Bone healing is a spatiotemporally regulated regeneration process, ideally leading to complete restoration of the broken bone without fibrous scar formation (1). Naturally, this regeneration process undergoes endochondral bone formation, if interfragmentary movements strain the fracture gap (2). In the majority of clinical cases, fracture healing follows the endochondral route and may be sub-divided into five phases, namely an (i) initial pro-inflammatory phase, (ii) antiinflammatory phase, (iii) fibrocartilaginous or soft callus phase, (iv) mineralization or hard callus phase and (v) remodeling phase in which bone tissue regains its physiological shape with a restored bone marrow cavity.…”
Section: Introductionmentioning
confidence: 99%
“…Using this approach, Checa et al (2011) and Borgiani et al (2015) showed that differences in the healing pattern (e.g., endosteal, periosteal, time to bringing) of different species (sheep, rat, and mice) can be explained by differences in the regulation of cellular activity by mechanical signals during the course of healing.…”
Section: The Role Of Cellular Activity On Tissue Formation Patternsmentioning
confidence: 99%